2001
DOI: 10.1351/pac200173060959
|View full text |Cite
|
Sign up to set email alerts
|

On the discovery of the elements 110-112 (IUPAC Technical Report)

Abstract: Republication or reproduction of this report or its storage and/or dissemination by electronic means isAbstract: The IUPAC/IUPAP joint working party on the priority of claims to the discovery of elements 110, 111, and 112 has reviewed the relevant literature pertaining to the several claims. In accordance with the criteria for the discovery of elements, previously established by the 1992 IUPAC/IUPAP Transfermium Working Group, it was determined that the claim by the Hofmann et al. research collaboration for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…JWP ASSESSMENT: The 1996 collaboration of Hofmann et al [5] combined with the 2002 collaboration of Hofmann et al [6] are accepted as the first evidence for the synthesis of element with atomic number 112, being supported by subsequent measurements of Morita et al [16,18], and by assignment of decay properties of likely hassium intermediates [9,11,13] in the decay chain originating from 277 112. tion studies using multi-GeV protons incident on a U target clearly indicated the production path was irreproducible as previously stressed [1,3,4]. The latter refutations have been challenged by Brandt [18,25], a member of the Marinov collaboration, in which he rejects the negative results because the same exact experiment as conducted by Marinov was not followed.…”
Section: Discovery Profilesmentioning
confidence: 91%
See 1 more Smart Citation
“…JWP ASSESSMENT: The 1996 collaboration of Hofmann et al [5] combined with the 2002 collaboration of Hofmann et al [6] are accepted as the first evidence for the synthesis of element with atomic number 112, being supported by subsequent measurements of Morita et al [16,18], and by assignment of decay properties of likely hassium intermediates [9,11,13] in the decay chain originating from 277 112. tion studies using multi-GeV protons incident on a U target clearly indicated the production path was irreproducible as previously stressed [1,3,4]. The latter refutations have been challenged by Brandt [18,25], a member of the Marinov collaboration, in which he rejects the negative results because the same exact experiment as conducted by Marinov was not followed.…”
Section: Discovery Profilesmentioning
confidence: 91%
“…As is customary in scientific analysis, and by rigorous practice now within the JWP, considerably more credence is given to content and date of publications that had been subjected to critical refereeing. Each profile begins with a reprise of the pertinent TWG [2] and JWP [3,4] content, if any. The element atomic number is in boldface followed by sequentially enumerated comment labels.…”
Section: Discovery Profilesmentioning
confidence: 99%
“…These have served effectively as guiding principles since then by subsequent JWPs [1,[3][4][5][6]. In our considerations, positive factors include low background events, cross-bombardments, excitation functions, internal reproducibility in productions and in decays, physicochemical behavior, spatial correlations of evaporation residues and subsequent decays, and separators distinguishing Z-values.…”
Section: Criteriamentioning
confidence: 99%
“…These Criteria have served effectively as guiding principles by subsequent JWPs [2][3][4][5]. Those references should be consulted by interested parties as the Criteria serve to provide a uniform, consistent basis for definitive observation and interpretation that is generally agreed to by investigators.…”
Section: However We Would Waive This Requirement Only In Cases Wherementioning
confidence: 99%
“…Each concise profile begins with a reprise of the pertinent content from earlier reports [1][2][3][4][5] if any. An historical account of the relevant publications on each element is given appended with the JWP's consensus opinion(s) as to the value of the evidence on the basis of the Criteria.…”
Section: Discovery Profilesmentioning
confidence: 99%